Sowing the seeds of change : the story of the Community Food Bank of Southern Arizona - Schindler, Seth (Sentinel Peak an imprint of University of Arizona Press, 2022)
"Sowing the Seeds of Change is the story of a remarkable organization's sustained, compassionate response to a problem of staggering proportions-food insecurity. The success of the Community Food Bank of Southern Arizona demonstrates that the war against hunger, however difficult, is winnable"--